Pengaruh Profesionalisme, Independensi dan Pelatihan Auditor Terhadap Kinerja Auditor Pada Kantor Akuntan Publik Provinsi Bali - Devi, Ni Putu Haris Candra; Pande Dwiana Putra, I Made (E-Jurnal Akuntansi; Vol 27 No 2 (2019), 2019)
The purpose of this study is to obtain empirical evidence of the influence of professionalism, independence and auditor training on auditor performance. The location of this research is at the Public Accountant Office (KAP) in Bali Province in 2018 and has been registered with the Indonesian Institute of Certified Public Accountants (IAPI). The method of determining the sample used in this study is the saturated sample method. The method of data collection in this study is the questionnaire method. The data analysis technique used in this study is multiple linear regression analysis. Based on the results of multiple linear regression analysis shows that professionalism, independence and auditor training have a positive effect on auditor performance. This research is expected to provide more in-depth information and understanding, and it is hoped that the auditor can uphold the professionalism and independence when conducting audits, so that the auditor's performance will be good. Keywords: Professionalism, independence, auditor training, auditor performance